Competence approach and a credit-modular system of training - Dmitriy V. Afanasiev; Vladimir Sergeevich Gryzlov (Высшее образование в России)
The paper offers a variant of implementing a competence approach within a credit-modular system of training in accordance with the Federal State Educational Standards (FSES). As an example, it presents a logical consequence of forming general cultural and professional competences in the major 270800 “Construction” through a set of academic, calendar and discipline modules. A variant of evaluating competences is offered, as well as the curriculum modular structure.